Transformation of Stilbene Glucosides From Reynoutria multiflora During Processing - Bai, Junqi; Chen, Wanting; Huang, Juan; Su, He; Zhang, Danchun; Xu, Wen; Zhang, Jing; Huang, Zhihai; Qiu, Xiaohui (Frontiers in Pharmacology, 2022)
The root of Reynoutria multiflora (Thunb. RM) Moldenke has been widely used in TCM clinical practice for centuries. The raw Reynoutria multiflora (RRM) should be processed by steaming or simmering before use, in order to reduce toxicity and increase efficiency. However the content of trans-2, 3, 5, 4′-tetrahydroxystilbene-2-O-β-D-glucopyranoside (trans-THSG), which is considered to be the main medicinal ingredient, decreases in this process. A simple and effective method was developed for characterization of stilbene glucoside compounds in RRM and the processed Reynoutria multiflora (PRM) by ultra high performance liquid chromatography tandem quadrupole/electrostatic field orbitrap high-resolution mass spectrometry (UHPLC-Q-Exactive plus orbitrap MS/MS). The content and quantity of stilbene glycoside compounds have undergone tremendous changes during the processing process. The metabolic process of 7 stilbene glycosides in RM was speculated, 55 substituents were identified, and the production of 5-HMF and a series of its derivatives were also speculated. 146 stilbene glycoside compounds were detected in RRM, 198 compounds were detected in PRM for 4h, 210 compounds were detected in PRM for 8h and 218 compounds were detected in PRM for 12h, 219 stilbene glycosides derivatives were identified after PRM for 18 h~32 h, of which 102 stilbene glycoside compounds may be potential new compounds. And the changing trend of the compounds can be summarized in 3 forms: gradually increased, gradually decreased, first or first increased and then decreased. The content of trans-THSG was indeed decreased during processing, but it was converted into a series of derivatives through the esterification reaction with small molecular compounds. Conclusion: Although the content of each derivative was relatively low, it would be metabolized into the same metabolites as THSG in vivo, which could prove that THSG was only converted, not completely degraded, it should not be the toxic component.